Argumentative Discourse: A Problem in English- Arabic Translation - EUTAMENE, Naima (Journal of Human Sciences, 2015)
The translation of argumentative texts is not difficulties free.Learners of English as a foreign language most often fail to transfer the pragmatic content which is expressed to the target language. This paper aims at highlighting the links between pragmatic knowledge and the strategies involved in the performance of EFL learners in translating argumentative texts. In this connection, an experimental design has been opted for in which an experimental group and a control group of third year students of English,(40 students per each) take a pre-test and a post-test. The testees of the experimental group show a remarkable development in their translation performance after theywere trained to translate four argumentative texts into Arabic in addition to being exposed to theoretical background about speech acts, argumentation and translation. On the contrary, the respondents of the control group keep on encountering the same difficulties in the pretest and the post-test with no change in their performance. This proves that there is a strong correlation between enhancing learners’ theoretical knowledge about speech acts, argumentation and translation and learners performance in translating argumentative discourse.